Evaluation of standard and real fire exposures on thermal response of rail car floor assembly. (2nd December 2019) - Kapahi, Anil; McKinnon, Mark; Lattimer, Brian
Summary: This work developed a computational methodology to evaluate and compare standard fire exposures such as those outlined in ASTM E119 with real fire exposures and determine the difference in the temperature rise of a rail car floor assembly. The real fire exposures simulated in this work were identified in a review of incidents and consisted of a constantly‐fed diesel fuel spill, a localized trash fire, and a gasoline spill simulated from a collision of the railcar with an automobile. These realistic fire exposures were applied to a variety of exemplar rail cars representative of single‐level and bi‐level passenger cars. These floor assembly models exposed to realistic fires were simulated in Fire Dynamics Simulator (FDS). The thermal exposure at the underside of railcar provided by FDS was coupled with a thermal model in ABAQUS, which provided the evolution of temperature in different components of the floor assembly. The standard scenarios were simulated for 2 hours instead of the typical 30 minutes to identify the appropriate exposure duration in ASTM E119, which can better represent a real fire scenario. The average and maximum temperatures predicted at the unexposed surface for both scenarios were compared with the threshold values given in NFPA 130.